2020
DOI: 10.1002/jlcr.3866
|View full text |Cite
|
Sign up to set email alerts
|

Development of a fully automated low‐pressure [11C]CO carbonylation apparatus

Abstract: carbon monoxide ([ 11 C]CO) is a versatile synthon for radiolabeling of drug-like molecules for imaging studies with positron emission tomography (PET). We here report the development of a novel, user-friendly, fully automated, and good manufacturing practice (GMP) compliant low-pressure synthesis module for 11 C-carbonylation reactions using [ 11 C]CO. In this synthesis module, [ 11 C]CO was reliably prepared from cyclotron-produced [ 11 C]carbon dioxide ([ 11 C]CO 2) by reduction over heated molybdenum and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…We hypothesized that these challenges could be alleviated by leveraging the more ready availability of [ 11 C]CO from modern cyclotrons (e.g., utilizing the Process Cabinet of a GE PETtrace) and developing methods that are compatible with the automated synthesis modules used for cGMP manufacture of PET radiotracers today. Thus, we and others are motivated to develop more user-friendly approaches for 11 C-carbonylation (28,(39)(40)(41). Notably, concurrent with our efforts, Lindberg et al demonstrated that [ 11 C]ibrutinib can be prepared via 11 C-carbonylation in a reactor method (40), and reported preliminary pre-clinical imaging results comparable to our earlier findings (29).…”
Section: Introductionsupporting
confidence: 69%
“…We hypothesized that these challenges could be alleviated by leveraging the more ready availability of [ 11 C]CO from modern cyclotrons (e.g., utilizing the Process Cabinet of a GE PETtrace) and developing methods that are compatible with the automated synthesis modules used for cGMP manufacture of PET radiotracers today. Thus, we and others are motivated to develop more user-friendly approaches for 11 C-carbonylation (28,(39)(40)(41). Notably, concurrent with our efforts, Lindberg et al demonstrated that [ 11 C]ibrutinib can be prepared via 11 C-carbonylation in a reactor method (40), and reported preliminary pre-clinical imaging results comparable to our earlier findings (29).…”
Section: Introductionsupporting
confidence: 69%
“…It is worth noting that the aqueous hydrolysis step could be eliminated in this setting, possibly due to the use of non‐anhydrous TFA for the deprotection. The radiosynthesis of these drug molecules was performed according to good manufacturing practice (GMP) on a recently developed fully automated and commercially available radiochemistry system for low pressure radiocarbonylation [19] . Gratifyingly, both compounds were radiolabeled in sufficient quantity and quality to enable preclinical studies in non‐human primates.…”
Section: Resultsmentioning
confidence: 99%
“…The radioactivity was transferred from the target to a TracerMaker synthesizer (ScanSys Laboratorieteknik ApS). The fully automated production of [ 11 C]CO was performed according to previously reported methods 4–6 . The produced [ 11 C]CO 2 was concentrated in a cryogenic trap and reduced to [ 11 C]CO by passing it through a molybdenum column (preheated at ~850°C).…”
Section: Methodsmentioning
confidence: 99%
“…The fully automated production of [ 11 C]CO was performed according to previously reported methods. [4][5][6] The produced [ 11 C]CO 2 was concentrated in a cryogenic trap and reduced to [ 11 C]CO by passing it through a molybdenum column (preheated at $850 C). The produced [ 11 C]CO was then concentrated in a cryogenic silica trap.…”
Section: Production Of [ 11 C]comentioning
confidence: 99%